A identificação fonêmica do discurso de estudantes brasileiros na língua russa (Revista de Estudos da Linguagem, 2004)
The Portuguese language, in the discourse of Brazilians, has specificfeatures that are manifest in a more evident form in its lexis andphonetics, which allows us to speak, therefore, of a BrazilianPortuguese. Leaving aside the discussion of the status of BrazilianPortuguese, we must take into consideration the indisputably broadvariability of its phonetic system, which is due not only to linguisticbut also to sociolinguistic factors, which, in their turn, cannot buthave an influence on the phonetic formation of Brazilian discourseduring, for example, the learning of the Russian language (RL).Besides, the written form of some letters, both in Portuguese andRussian, causes not only phonetic but also graphic-phoneticinterference to arise whether during reading, writing, or oral discourse. The specifics of the native language of Brazilians istransferred to the discourse in the RL, mainly during the initialstage of learning. Research on the phonetic interference of thediscourse of Brazilians who study the RL, is still in the early phase,but, even so, through the experimental results already obtained,we can speak of the specific and universal features of itsmanifestation. A priori, these violations have an orthoepic andorthophonic character, for they have a lot to do with the differentialand integral criteria of the phonemes, since these violations mayoccur because of the specific distributive and phonotactical relationsof the languages in question. The sources of the errors can besubjectively defined by the manner in which the learner assimilaresand perceives the physical and linguistic functions of both languages.Both in written and oral discourse, the action of graphic-phoneticinterference is observed.